A Framework for Understanding Marine Cosmopolitanism in the Anthropocene - Darling, John A.; Carlton, James T. (Frontiers in Marine Science, 2018)
Recent years have witnessed growing appreciation for the ways in which human-mediated species introductions have reshaped marine biogeography. Despite this we have yet to grapple fully with the scale and impact of anthropogenic dispersal in both creating and determining contemporary distributions of marine taxa. In particular, the past several decades of research on marine biological invasions have revealed that broad geographic distributions of coastal marine organisms—historically referred to simply as “cosmopolitanism”—may belie complex interplay of both natural and anthropogenic processes. Here we describe a framework for understanding contemporary cosmopolitanism, informed by a synthesis of the marine bioinvasion literature. Our framework defines several novel categories in an attempt to provide a unified terminology for discussing cosmopolitan distributions in the world's oceans. We reserve the term eucosmopolitan to refer to those species for which data exist to support a true, natural, and prehistorically global (or extremely broad) distribution. While in the past this has been the default assumption for species observed to exhibit contemporary cosmopolitan distributions, we argue that given recent advances in marine invasion science this assignment should require positive evidence. In contrast, neocosmopolitan describes those species that have demonstrably achieved extensive geographic ranges only through historical anthropogenic dispersal, often facilitated over centuries of human maritime traffic. We discuss the history and human geography underpinning these neocosmopolitan distributions, and illustrate the extent to which these factors may have altered natural biogeographic patterns. We define the category pseudocosmopolitan to encompass taxa for which a broad distribution is determined (typically after molecular investigation) to reflect multiple, sometimes regionally endemic, lineages with uncertain taxonomic status; such species may remain cosmopolitan only so long as taxonomic uncertainty persists, after which they may splinter into multiple geographically restricted species. We discuss the methods employed to identify such species and to resolve both their taxonomic status and their biogeographic histories. We argue that recognizing these different types of cosmopolitanism, and the important role that invasion science has played in understanding them, is critically important for the future study of both historical and modern marine biogeography, ecology, and biodiversity.